Challenges and opportunities in establishing a collaborative multisite observational study of chronic diseases and lifestyle factors among adults in Puerto Rico - Josiemer Mattei; José F. Rodríguez-Orengo; Martha Tamez; Francheska Corujo; Aida Claudio; Héctor Villanueva; Hannia Campos; Walter C. Willett; Katherine L. Tucker; Carlos F. Ríos-Bedoya (BMC, 2017)
Abstract Background Prevalence of chronic diseases and unhealthy lifestyle behaviors among the adult population of Puerto Rico (PR) is high; however, few epidemiological studies have been conducted to address these. We aimed to document the methods and operation of establishing a multisite cross-sectional study of chronic diseases and risk factors in PR, in partnership with academic, community, clinical, and research institutions. Methods The Puerto Rico Assessment of Diet, Lifestyle and Diseases (PRADLAD) documented lifestyle and health characteristics of adults living in PR, with the goal of informing future epidemiological and intervention projects, as well as public health, policy, and clinical efforts to help improve the population's health. The study was conducted in three primary care clinics in the San Juan, PR metropolitan area. Eligible volunteers were 30-75y, living in PR for at least 10 months of the previous year, and able to answer interviewer-administered questionnaires without assistance. Questions were recorded electronically by trained interviewers, and included socio-demographic characteristics, lifestyle behaviors, self-reported medically-diagnosed diseases, and psychosocial factors. Waist and hip circumferences were measured following standardized protocols. A subset of participants answered a validated food frequency questionnaire, a legumes questionnaire, and had medical record data abstracted. Process and outcome evaluation indicators were assessed. Results The study screened 403 participants in 5 months. Of these, 396 (98%) were eligible and 380 (94%) had reliable and complete information. A subset of 242 participants had valid dietary data, and 236 had medical record data. The mean time to complete an interview was 1.5 h. Participants were generally cooperative and research collaborators were fully engaged. Having multiple sites helped enhance recruitment and sociodemographic representation. Diagnosed conditions were prevalent across sites. Challenges in data monitoring, interviewer training, and scheduling were identified and corrected, and should be addressed in future studies. Conclusions Epidemiological studies in PR can be successfully implemented in partnership with multiple institutions. Effective recruitment and implementation requires concerted planning and continued involvement from partners, frequent quality control, brief interviews, reasonable incentives, and thorough training/re-training of culturally-sensitive interviewers. Further studies are feasible and needed to help address highly prevalent chronic conditions in PR.